Epiphytic macrolichen as indicators of environmental changes in a montane forest of Panama - Vissuetti , Ana (2025)
Introduction: Corticolous lichens are organisms that respond to habitat modifications, which is why they are considered model organisms to evaluate environmental changes in different ecosystems. Objectives: To determine the species richness and community composition of corticolous macro lichens in montane forests and forest remnants. In addition, the effect of microclimatic factors in three areas with different degrees of light intensity and density of arboreous vegetation on the species distribution of recorded diversity was evaluated. Methods: The study was conducted in the Volcan Baru National Park, Panama. Three areas with different forest densities and host tree species, Comarostaphylis arbutoides and Quercus spp., were chosen, considering a total of 60 trees, 10 of each species in each area. The canopy's opening close to the host trees and its diameter at breast height were recorded. Linear models and multivariate analysis was used to determine changes in species richness and composition of epiphytic macro lichens. Results: The characteristics of the host trees (e.g. host species and area) conditioned the species richness, while the communities were limited by microclimatic changes (e.g. light) in different areas. Conclusion: The macro lichens communities analyzed responded to changes related to the host tree species and the microclimate, so they can be considered indicators of ecological continuity in tropical montane forests.